Tuition-Waiver Policies for Older Learners in University Courses: Past Practices, Current Developments and Future Prospects - Thompson, Gordon (Canadian Journal of Higher Education, 2003)
Over the past 30 years, many universities in Canada and the United States have introduced tuition-waiver policies for older adults. This article reviews the literature describing the development and outcomes of these programs. Although several national surveys of tuition-waiver programs have been reported in the United States, none have previously been reported for Canadian universities. This article reports the results of the first such survey. Despite the widespread availability of tuition- waiver programs in Canada and the United States, it is clear that such programs have failed to attract significant numbers of older learners. The paper examines the causes and the implications of this failure.